Effects of plant growth regulators and growing media on propagation and field establishment of Stevia rebaudiana: a medicinal plant of commerce - K. Abha Manohar; Gopal Shukla; Bidhan Roy; Sumit Chakravarty (CABI Agriculture and Bioscience)
Abstract Background Stevia rebaudiana is an economically important medicinal plant that has generated interest among the growers and pharmacologists in terms of its industrial or pharmaceutical value. For the mass production of the seedlings, easy and convenient techniques are lacking while, micro propagation was reported promising but still out of reach at farm level. The unavailability of quality planting materials due to non-viable seeds is restricting its mass commercial scale cultivation. The present study was therefore attempted to standardize the plant growth regulators and growing media to standardize the vegetative propagation protocol through cuttings for its mass multiplication in Terai region of West Bengal, India. Methods Growing media (soil, FYM, saw dust and sand) as sole and in combination and growth hormones (IAA, IBA and NAA in different concentration and a commercial formulation i.e. Totoroot© with different exposure time) were compared with control (i.e. sole soil and no hormone treatment, respectively) to standardize the nursery protocol of Stevia. Results Sand used as sole was found the best growing media for survival and growth of cuttings while, cuttings treated with commercial growth hormone formulation for 5 mins was best. Cuttings treated with commercial growth hormone formulation performed significantly better in the field with respect to survival, growth and production of leaves. Conclusion The study recommends the use of sole sand media and commercial growth hormone formulation with 5 mins exposure time for mass nursery production of Stevia cuttings in Terai zone of West Bengal due to their better performance both in the nursery and after transplanting in the field.